An Encounter between a Teacher and Child with ASD in a Pre-School Environment - Juškienė, Vaiva; Voidogaitė, Viktorija (Acta Paedagogica Vilnensia, 2021)
The article focuses on the phenomenon of the first meeting between an educator and a child on the autism spectrum and the an educator’s experiences during the encounter. An analysis of the scientific literature shows that the number of autistic children in Lithuania is increasing. The text describes a meeting between a pre-school and a pre-primary school educator and a child with autism spectrum disorders. The analysis unfolds the experience of particular educators when they meet a child with ASD in an ordinary pre-school group. During a hermeneutical phenomenological analysis, the experience of the educators are based on two existential subjects: experienced relationship and experienced body. During the first meeting with a child with ASD, educators attempted to establish a relationship with the child. Although each participant of the analysis experienced this beginning individually, all of them were confronted with a challenge in communication while establishing these relationships. Autistic children avoided the methods of relation contracting that were usual to educators. When educators contacted with the autistic children, their experience unfolded through the children’s bodily experience (appearance and behaviour).